Achieving gender parity in academic leadership - Mohd Adnan, Normala (Star Media Group Berhad, 2024)
The recent report on gender disparity in leadership within Malaysian higher education highlights a pressing institutional issue. While women account for nearly 60% of public university lecturers, their representation in leadership positions remains disproportionately low at 36%. This imbalance not only limits the academic community's potential but also reflects deeply rooted structural and cultural biases. Addressing these challenges requires building on the commendable efforts already implemented by the Malaysian government while adopting more comprehensive strategies informed by global best practices.